Evaluation of sheep blood as nutritive suplement in culture media: citratated and defibrinated - Alejandro Vladimir Chacón Martén (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Sheep blood is an essential supplement in the elaboration of culture media, as it provides important nutritional factors for the growth and recovery of different organisms. Objective: To evaluate comparatively the effect of sheep citrated and defibrinated sheep blood in culture media with agar base as for the bacterial growth and the production of hemolysis in reference strains from different pathogen bacteria,                            as well as the recovery or isolation of microorganisms from clinical samples. Method: An observational, descriptive and cross-sectional was carried out in 6 microbiology laboratories in Santiago de Cuba city during 2017, in which male sheeps blood from the pelibuey breed for elaborating culture media. Each laboratory received either citrated blood or defibrinated and a survey was delivered to evaluate the results. Results: There was a better growing and bacterial isolation in the media supplemented with defibrinated blood, although yielding or results were favorable with citrated blood. Conclusions: The pertinence of the use of defibrinated blood as a supplement of nutritive enrichment in culture media was confirmed; however, the use of citrated blood was demonstrated in the routine work of the clinical microbiology laboratory.